THE IDENTIFICATION OF THE UNTUNG JAWA ISLAND’S INFRASTRUCTURE, LOCAL POTENTIALS AND ECOLOGICAL ASPECT FOR THE DEVELOPMENT OF AN ECOLOGICAL BASED INFRASTRUCTURE - Puro, Sarjono; Atmiwyastuti, Niken; Restina, Nina (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2014)
Geographically, the Untung Jawa island is located at the Seribu Islands region, a maritime tourism spot at thenorth of Jakarta. The development of new infrastructures in the island would benefit to not only for tourism,but also the activities environmental sustainability in the area. A sustainable tourism development must touchthree important aspects: First, economic, social and environment which are inter-related to each other. If notcarried out in a balanced way, then it could possibly damage the infrastructures around the tourism area, suchas breakwaters, piers and the whole environment. In conclusion, it is important to map the characteristics ofthe infrastructure damage around the Untung Jawa Island, as well as the urgency to update the informationabout the ecology of the islands without forgetting the government’s role to develop the island by consideringthe characteristics of the infrastructure, local and ecological potential.